Bringing “Together”: Emotions and Power in Organizational Responses to Institutional Complexity - Sadeh, Linda Jakob; Zilber, Tammar B. (Academy of Management Journal, 2019)
The theoretical puzzle of how organizations deal with contradicting logics has been extensively investigated during the past two decades. This stream of research has focused on the cognitive, but has overlooked emotions and power, which are fundamental to the lived experience of logics, and to their constitution. Drawing on a 15-month ethnography of “Together,” a Jewish–Palestinian organization in a mixed city in Israel, we explore how the organization succeeds in challenging societal dominant notions of ethno-nationalism by stimulating universalistic notions, and how it occasionally fails to do so, as ethno-nationalism creeps in. Our findings indicate that emotional control allows organizations to deal with contradictory logics and achieve their desired constellation, while unbidden emotions disrupt local efforts and enable changes in desired constellations of logics. Further, systemic power mediates the very experience of logics and the prospects of changing their constellation: Social asymmetry necessitates harder emotion work on behalf of the underprivileged, differentiating their experience of logics, and limiting the extent to which emotional eruption is a viable option. Thus, our study highlights the intersection of logics, emotions, and power, and how logics are managed and failed to be managed.